2014
DOI: 10.1140/epjb/e2014-40787-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of superconductivity by an external magnetic field in magnetic alloys

Abstract: Abstract. An infinite-volume limit solution of the thermodynamics of a BCS superconductor containing spin 1/2 and 7/2 magnetic impurities, obtained recently in [D. Borycki, J. Maćkowiak, Supercond. Sci. Technol. 24, 035007 (2011)] is exploited to derive the expressions for critical magnetic field Hc(T ). The credibility of the resulting thermodynamically limited theoretical equations, which depend on the magnetic coupling constant g and impurity concentration c, is verified on the experimental data for the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…Therefore, it could be expected that a time independent (static) observable like the fluctuation magnetic susceptibility ∆χ will be unaffected by magnetic impurities, apart from the effects associated to possible changes in the superconducting parameters (for a recent theoretical work on this issue see, e.g., Ref. [11]). This is in fact the case of high-T c cuprates: recent measurements [12] have shown that the fluctuation diamagnetism of optimally-doped YBa 2 Cu 3 O 7−δ is not appreciably affected by the presence of magnetic impurities (both in the CuO 2 planes or intercalated between them).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it could be expected that a time independent (static) observable like the fluctuation magnetic susceptibility ∆χ will be unaffected by magnetic impurities, apart from the effects associated to possible changes in the superconducting parameters (for a recent theoretical work on this issue see, e.g., Ref. [11]). This is in fact the case of high-T c cuprates: recent measurements [12] have shown that the fluctuation diamagnetism of optimally-doped YBa 2 Cu 3 O 7−δ is not appreciably affected by the presence of magnetic impurities (both in the CuO 2 planes or intercalated between them).…”
Section: Introductionmentioning
confidence: 99%